Pond life; a guide to common plants and animals of North American ponds and lakes - Reid, George Kell.; Dolan, Tom; Kaicher, Sally Diana (New York, Golden Press, 1967)
A handbook describing and illustrating some of the common animals and plants found in or near ponds, lakes, streams, and marshes.
1 13 18 28
Keywords: Freshwater biology; Freshwater plants; Ponds of North America; Animals of ponds; plant life on ponds; Freshwater animals